PENDIDIKAN ISLAM SEBAGAI MANIFESTASI KEPEMIMPINAN DUNIA - Mawaddah, Afifatin (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract: This writing aims to explain about Islamic education as a manifestation (manifestation) of leadership in all corners of the world. Islamic education is a means of forming whole individuals who are able to internalize spiritual and physical values. The success of an education can be seen from how a leader in implementing community norms and environment. In essence every human being who lives is a leader. It's just that not all humans are able to become good, charismatic and intellectual leaders. The method used in this writing is the method of literature or literature from articles, journals and thesis. Data collection techniques are done by searching various sources of literature and documents that are assembled. This writing is designed based on the existing background, which is why Islamic education can be said to be world leadership. The Islamic view itself is a leader who can influence its members. In the case of a leader in the world of Islamic education is a teacher. Teachers can be called murabby or nurture, manage and maintain. Murabby comes from the root word rabba-yurabby which means rabbul alamin (God).